Biology - Chia, Lok Thye; Jacqueline R.S; Nalini B. (Ace Ahead STPM text, 2018)
This book is specially written for Sixth Form students taking Biology Paper 1 in the STPM examination. It contain all the topics stipulated in the latest syllabus for First Term.